Anchored hybrid enrichment challenges the traditional classification of flesh flies (Diptera: Sarcophagidae). (31st October 2019) - Buenaventura, Eliana; Szpila, Krzysztof; Cassel, Brian K.; Wiegmann, Brian M.; Pape, Thomas
Abstract: Sarcophagidae is one of the most species‐rich families within the superfamily Oestroidea. This diversity is usually represented by three lineages: Miltogramminae, Paramacronychiinae and Sarcophaginae. Historically, the phylogenetic relationships among these lineages have been elusive, due to poorly supported hypotheses or small taxon sets, or both. This study provides a dramatic increase in molecular data, more balanced sampling of all three lineages from all biogeographical regions and a reassessment of morphological characters using scanning electron microscopy in the most comprehensive assessment of subfamily‐level phylogeny in Sarcophagidae to date. This analysis of the largest molecular dataset ever produced for a phylogenetic analysis of a fly lineage, with 950 loci from anchored hybrid enrichment comprising 435 930 bp from 101 species, revealed Paramacronychiinae as sister to Miltogramminae, not to Sarcophaginae, as suggested by adult morphology. Maximum likelihood analysis produced a well‐supported topology, with 91% of the nodes receiving strong bootstrap proportions (> 97%). In contrast to the molecular data, three out of nine morphological characters studied point to a sister‐group relationship of (Sarcophaginae + Paramacronychiinae) and the remaining six characters are either silent on subfamily relationships or in need of further study. Re‐examination of morphological structures provides new insights into the evolution of male genitalic traits within Sarcophagidae and highlights their convergence producing conflicting phylogenetic signal. Our phylogeny reconciles older and widely used systems of classification with tree‐based thinking and sets up a classification of flesh flies that is more aligned with their evolutionary history. Abstract : We analyse the largest molecular dataset ever produced for the phylogenetic analysis of a fly lineage, with 950 loci from anchored hybrid enrichment comprising 435 930 bp from 101 species. The analysis revealed Paramacronychiinae as sister to Miltogramminae, not to Sarcophaginae, as suggested by adult morphology. Re‐examination of morphological structures provides new insights into the evolution of male genitalic traits within Sarcophagidae and highlights their convergence producing conflicting phylogenetic signal.